2012
DOI: 10.1111/j.1532-5415.2012.04120.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Timed Up‐and‐Go and Memory, Executive Function, and Processing Speed

Abstract: Slower TUG time is independently associated with poorer performance on global cognition, executive function, and memory tests and slower processing speed. This highlights that TUG is more than just a simple mobility task and suggests that a comprehensive cognitive assessment is important for individuals with mobility difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 31 publications
9
118
0
Order By: Relevance
“…12,13 Greene and colleagues focused on change in test results over time in 189 community dwelling older adults. 12,13 They reported that TUG and the BBS scores were not significantly associated with CD after 2 years follow-up, but rather the change from baseline to follow-up in TUG parameters was independently and significantly associated with CD. It is possible that in our population the stroke may have triggered or unmasked underlying neurodegenerative processes.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Greene and colleagues focused on change in test results over time in 189 community dwelling older adults. 12,13 They reported that TUG and the BBS scores were not significantly associated with CD after 2 years follow-up, but rather the change from baseline to follow-up in TUG parameters was independently and significantly associated with CD. It is possible that in our population the stroke may have triggered or unmasked underlying neurodegenerative processes.…”
Section: Strokementioning
confidence: 99%
“…This relationship can be explained by the idea that the TUG relies on the interplay between attention, executive function, and motor processing functions. 5,12,15 Moreover, dual-task during gait may be a marker of the efficiency of the central integration of multiple cognitive domains needed for this complex task.…”
Section: Strokementioning
confidence: 99%
“…Our findings build on previous research in several ways. First, studies in samples without serious mental illness found a similar association between slower TGUG and poorer performance on speed of processing tests (Donoghue et al, 2012; Herman, Giladi, & Hausdorff, 2011) and memory tests (Donoghue et al, 2012). Second, after adjusting for covariates (including age), Donoghue et al (2012) also reported significant associations between TGUG time and speed of processing.…”
Section: Discussionmentioning
confidence: 92%
“…First, studies in samples without serious mental illness found a similar association between slower TGUG and poorer performance on speed of processing tests (Donoghue et al, 2012; Herman, Giladi, & Hausdorff, 2011) and memory tests (Donoghue et al, 2012). Second, after adjusting for covariates (including age), Donoghue et al (2012) also reported significant associations between TGUG time and speed of processing. Furthermore, although there is a lack of research on the association of mobility and cognition in older adults with schizophrenia, a small (n=17) study in patients with early schizophrenia (mean age 30) showed a significant univariate association between TGUG time with cognitive function (measured with the MMSE and a Frontal Assessment Battery) (Lallart et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Hence, researchers [1][2][3][4] using different indexes such as reaction time and error rate are try ing to correct these factors. The reaction t ime is an important index that is usually used in the tests of human performance such as Simp le Reaction Time test (SRT) [5], Diagnostic Reaction Time test (DRT), Choice Reaction Time test (CRT) [5,6], Continuous Performance Task (CPT) [7], Test of Variab les of Attention (TOVA) [8,9], Attention Network Test (ANT) [9][10][11] and Wisconsin Card Sort ing Test (WCST) [1]. In fact, this index is applied for measuring the amount of normality (e.g.…”
Section: Introductionmentioning
confidence: 99%